Hurricane-Damaged Palms in the Landscape: Care after the Storm - Monica L. Elliott; Timothy Broschat (EDIS)
While many palm species are adapted to windstorms, a hurricane can damage even the most tolerant palms. This 3-page fact sheet provides suggestions about what to do after a windstorm has occurred once it is safe to venture outside to care for the landscape. Written by Monica L. Elliott and Timothy Broschat, and published by the UF Department of Environmental Horticulture, September 2012.